Sensitifitas gender dalam pembelajaran PAI berbasis nilai-nilai pendidikan multikultural di SD al-Irsyad al-Islamiyah 01 Purwokerto - Ahmad Sahnan (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2020)
This study aims to analyze the multiculturalism in Islamic Primary school (learning PAI at SD al-Irsyad al-Islamiyah 01 Purwokerto). The data in this study were collected through interview techniques, observation, documentation. The collected data is combined with the triangulation technique. The results of multiculturalism research in Islamic primary school at SD al-Irsyad al-Islamiyah 01 Purwokerto show the following: first, Multiculturalism in learning PAI at SD al-Irsyad al-Islamiyah 01 Purwokerto is well contained. Second, the nuances of multiculturalism are found in the teacher's understanding, learning methods, teaching materials, media use, methods, and class organization. Third, the implications for students' understanding in the PAI learning process already contain multicultural values ​​(democracy, tolerance, justice, equality/gender, and togetherness). Fourth, multicultural actualization is found in classroom learning and extracurricular activities. The learning process and activities at primary school that take place provide space for the achievement of the realization of multicultural values ​​which include: (1) Internalization of multicultural values ​​delivered in the learning process of PAI. (2) The teacher provides equal opportunities to each student in developing their potential in the learning process. (3) Opportunities given fairly without discriminating with one another.